Increased Metabolic Burden Among Blacks: A Putative Mechanism for Disparate COVID-19 Outcomes - Jean-Louis G (Dove Medical Press, 2020)
Girardin Jean-Louis,1 Arlener D Turner,1 Peng Jin,2 Mengling Liu,2 Carla Boutin-Foster,3 Samy I McFarlane,3 Azizi Seixas1 1Departments of Population Health, Psychiatry, and Biostatistics, New York University Langone Health, New York, NY, USA; 2Department of Biostatistics, New York University Langone Health, New York, NY, USA; 3Departments of Medicine and Endocrinology, SUNY Downstate Medical Center, New York, NY, USACorrespondence: Girardin Jean-LouisNYU Grossman School of Medicine, 180 Madison Avenue, 7th Floor, New York, NY 10016, USATel +1 646.501.3431Email Girardin.Jean-Louis@nyulangone.orgAbstract: Mounting evidence shows a disproportionate COVID-19 burden among Blacks. Early findings indicate pre-existing metabolic burden (eg, obesity, hypertension and diabetes) as key drivers of COVID-19 severity. Since Blacks exhibit higher prevalence of metabolic burden, we examined the influence of metabolic syndrome on disparate COVID-19 burden. We analyzed data from a NIH-funded study to characterize metabolic burden among Blacks in New York (Metabolic Syndrome Outcome Study). Patients (n=1035) were recruited from outpatient clinics, where clinical and self-report data were obtained. The vast majority of the sample was overweight/obese (90%); diagnosed with hypertension (93%); dyslipidemia (72%); diabetes (61%); and nearly half of them were at risk for sleep apnea (48%). Older Blacks (age≥ 65 years) were characterized by higher levels of metabolic burden and co-morbidities (eg, heart disease, cancer). In multivariate-adjusted regression analyses, age was a significant (p≤ .001) independent predictor of hypertension (OR=1.06; 95% CI: 1.04– 1.09), diabetes (OR=1.03; 95% CI: 1.02– 1.04), and dyslipidemia (OR=0.98; 95% CI: 0.97– 0.99), but not obesity. Our study demonstrates an overwhelmingly high prevalence of the metabolic risk factors related to COVID-19 among Blacks in New York, highlighting disparate metabolic burden among Blacks as a possible mechanism conferring the greater burden of COVID-19 infection and mortality represented in published data.Keywords: COVID-19 burden, blacks, metabolic syndrome, metabolic risk factors, disparities